Clinical outcomes and severity of laboratory-confirmed RSV compared with influenza, parainfluenza and human metapneumovirus in Australian children attending secondary care - Kathryn Glass; Peter Richmond; Hannah C Moore; Mohinder Sarna; Huong Le; Avram Levy; Belaynew Wasie Taye (BMJ Open Respiratory Research)
Introduction Acute lower respiratory infections (ALRIs) are a major contributor to the global infectious disease burden and a common cause of hospitalisation for children under 2 years. We compared clinical severity in children hospitalised with respiratory syncytial virus (RSV), parainfluenza virus (PIV), human metapneumovirus (hMPV) and influenza virus (IFV).Methods We used a probabilistically linked population cohort born in Western Australia between 2010 and 2020 and hospitalised before the age of 2 years. Outcomes compared included length of hospital stay (LOS), admission to intensive care unit (ICU), need for respiratory support (RS), complex hospital course (RS, death, ICU admission or LOS >75th percentile), 7-day and 30-day mortality, hospital-in-the-home care, 30-day all-cause and ALRI-specific readmissions and emergency department presentations 14 days prior to hospitalisation. Logistic regression was used for binary outcomes, and negative binomial regression was used for discrete count variables. Incidence rates, time to RS and time to readmissions were calculated using survival analysis techniques.Results The final cohort included 210 997 hospitalised children under 24 months of age for a total of 315 769 admissions. Infants hospitalised before 6 months had the highest rates for all virus-specific hospitalisations, particularly RSV hospitalisations (50.4 per 1000 child-years (95% CI 48.7 to 52.1)). Infants <6 months had higher odds of an ICU admission (adjusted OR (aOR) 2.39, 95% CI 1.36 to 4.19) and RS (aOR 4.68, 95% CI 2.95 to 7.44) and a complex hospital course (aOR 2.69, 95% CI 2.13 to 3.42) with RSV and four times higher hazards of requiring RS earlier (adjusted HR (aHR) 4.06, 95% CI 2.59 to 6.36). An ALRI-coded 30-day readmission was recorded in 10%–24% of virus-specific hospitalisations.Discussion Young infants have a more severe and complex hospital course with RSV hospitalisation compared with hospitalisation with other respiratory viruses and should be prioritised for prevention measures such as the single-dose monoclonal antibody, nirsevimab.